(untitled) (Plant Tissue Culture and Biotechnology, 2014)
Efficient direct shoot regeneration of two pear (Pyrus communis L.), namely ’bartlett’ and ’dargazi’ was successfully developed for the use in future genetic engineering research. The basal MS and NN media supplemented with different concentrations of TDZ (0, 2.5, 5, 7.5 ?M) or BAP (0, 4, 8, 16 ?M) in combination with NAA (1 ?M) were compared. The result showed that direct adventitious shoot regeneration in pear was highly dependent on genotype, explant type and culture media. ’dargazi’ had higher rate of regeneration compared to ’bartlett’ and in both cultivars the highest per cent of regeneration was observed in lower sections of the leaves. Although the highest per cent of regeneration in ’bartlett’ (38) was attained in the NN medium containing 2.5 µM TDZ and 1 µM NAA, but the differences in shoot regeneration between media containing 5 or 7.5 µM TDZ and 1 µM NAA were not significant. The highest per cent of regeneration in ’dargazi’ (56) was obtained in NN medium containing 7.5 µm TDZ and 1 µm NAA. Plant Tissue Cult. & Biotech. 24(1): 87-92, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19215